Bio-Membrane SELEX as a New Approach for Selecting ss-DNA Aptamers that Bind to the Hydatid Cyst Laminated Layer - Dehkordi, Azar B.; Khanahmad, Hossein; Azizi, Yadollah; Mirian, Mina; Pestehchian, Nader; Darani, Hossein Yousofi (Current Molecular Medicine, 2023)
Background: Hydatid cyst (HC) is the larval stage of the canine intestinal tapeworm (cestode), Echinococcus granulosus. In addition to the high global economic cost of livestock farming, the infection can lead to dangerous problems for human health. Therefore, research into new diagnosis and treatment approaches is valuable. This study is set out to explore aptamers that bind to HC antigens. Methods: The similarity between HC genotype in sheep and humans was that sheep HCs were collected and used as a biological membrane for aptamer selection. Four Bio- Membrane SELEX rounds were conducted, and ssDNA aptamers were selected. Selected aptamers' affinity and specificity to the laminated layer antigens were evaluated using membrane staining by fluorescein primer as a probe. Biotinylated primer was used as a probe for aptahistochemistry and dot blot techniques. Subsequently, cloning and plasmid extraction was conducted. The affinity and specificity of sequenced aptamers were examined with the dot blot method. Results: Selected aptamers reacted with HC wall in aptahistochemistry, aptahistofluorescent, and dot blot experiments. Following cloning and sequencing, 20 sequences were achieved. A strong reaction between HC total antigens and sequenced aptamers has emerged in the dot blot method. Conclusion: We propose a novel method to determine specific aptamers in this investigation. Bio-Membrane SELEX could be assumed as a practical and sensitive method for aptamer selection. Selected aptamers in this study possibly may be used for specific HC antigens detection.
Keywords: Aptamer